2002
DOI: 10.1038/ng888
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic properties of PPM1D located within a breast cancer amplification epicenter at 17q23

Abstract: We found that PPM1D, encoding a serine/threonine protein phosphatase, lies within an epicenter of the region at 17q23 that is amplified in breast cancer. We show that overexpression of this gene confers two oncogenic phenotypes on cells in culture: attenuation of apoptosis induced by serum starvation and transformation of primary cells in cooperation with RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
213
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(223 citation statements)
references
References 13 publications
9
213
1
Order By: Relevance
“…Thus, although we expected to see a substantial tumorprone phenotype in MMTV-PPM1D transgenic mice, they actually remained tumor-free. This further supports the notion that Wip1 behaves as a modulator of tumorigenesis and a weak oncogene in vivo (Bulavin et al, 2002;Li et al, 2002). Wip1 overexpression using an MMTV promoter does not have any overt effect on mammary gland development.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Thus, although we expected to see a substantial tumorprone phenotype in MMTV-PPM1D transgenic mice, they actually remained tumor-free. This further supports the notion that Wip1 behaves as a modulator of tumorigenesis and a weak oncogene in vivo (Bulavin et al, 2002;Li et al, 2002). Wip1 overexpression using an MMTV promoter does not have any overt effect on mammary gland development.…”
supporting
confidence: 85%
“…Further evidence with a rodent fibroblast transformation assay showed that introduction of Wip1 along with Ras, Myc, or ErbB2 resulted in enhanced colony formation in soft agar and led to the development of tumors when these cells were explanted into nude mice (Bulavin et al, 2002). These findings suggested that Wip1 phosphatase has oncogenic potential (Bulavin et al, 2002;Li et al, 2002;Hirasawa et al, 2003;Saito-Ohara et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wip1 is induced by DNA damage in a p53-dependent manner, and inhibits ultraviolet (UV)-irradiation-induced p38 activation by dephosphorylating Thr180 in p38, thereby inhibiting the function of p53. 24,25 It has been reported that the Wip1 (PPM1D) gene is amplified or overexpressed in various human cancers, including breast cancers, [26][27][28][29] and that overexpression of Wip1 (PPM1D) complements the oncogenes Ras, Myc, and Neu1 for transformation of wild-type mouse embryonic fibroblasts (MEFs). 26 More recently, it has been shown that Wip1 associates with the nuclear isoform of uracil DNA glycosylase, UNG2, and that Wip1 suppresses DNA damage-induced base excision repair (BER) activity by dephosphorylating and inactivating UNG2.…”
Section: Introductionmentioning
confidence: 99%
“…PS6K is a ribosomal protein that is involved in the progression from the G1 to S phase of the cell cycle. It is rapidly activated in response to mitogenic stimuli, for example, growth factors, cytokines, and oncogene products (Grove et al, 1991;Lane et al, 1993;Chou et al, 1995;Grammer et al, 1996;Thomas et al, 1997;Couch et al, 1999;Barlund et al, 2000b;Wu et al, 2000;Latham et al, 2001;Monni et al, 2001;Andersen et al, 2002;Li et al, 2002;Sinclair et al, 2002;Sinclair et al, 2003).…”
mentioning
confidence: 99%